Factors That Influence Online Game Consumer Loyalty through Consumer Satisfaction - Zendrato, Bernadus Orudu Richard; Zakiya, Hani Fildzah; Usman, Osly (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to analyze the influence of product quality, product features, product style and design, brand image, and brand experience on consumer loyalty in the online gaming industry in the Depok, Bogor, Jakarta, Tangerang, Bekasi (Jabodetabek) area, with consumer satisfaction as an intervention variable. The results of data analysis show that online game product quality does not have a significant influence on consumer satisfaction, and the same thing applies to the direct influence of product quality on consumer loyalty. Online game product features also do not have a direct influence on consumer satisfaction and loyalty. Product style and design do not directly influence consumer satisfaction and loyalty in online games. However, brand image has a direct influence on consumer satisfaction, while brand experience has a direct influence on satisfaction. Consumer satisfaction, in turn, has a positive impact on consumer loyalty. Some factors, such as product quality, product features, and product style and design, may have an indirect influence on loyalty through satisfaction. Therefore, this research provides valuable insights for companies in developing marketing strategies and increasing consumer loyalty in the online gaming industry in the Depok, Bogor Jakarta, Tangerang, Bekasi (Jabodetabek) area.